Decoration of CdS nanoparticles on 3D self-assembled ZnO nanorods: a single-step process with enhanced field emission behaviour - Warule, Sambhaji S.; Chaudhari, Nilima S.; Shisode, Raju T.; Desa, Keith V.; Kale, Bharat B.; More, Mahendra A. (CrystEngComm, 2015)
A well-defined CdS-ZnO heteroarchitecture has been synthesized via a facile single-step hydrothermal approach. The morphological and structural studies reveal the formation of 3D nano-architectures, in which self-assembled ZnO nanorods (diameter similar to 50 nm) are well decorated with single crystalline CdS nanoparticles (size similar to 10 nm). The CdS-ZnO heteroarchitecture exhibits a remarkable change in the optical absorption due to the surface modification of ZnO nanorods by CdS. Surprisingly, under identical reaction conditions, the global ZnS nanoparticles are selectively grown at the apex of ZnO nanorods on the Zn substrate. Furthermore, a plausible growth mechanism has been presented on the basis of experimental results. Interestingly, the CdS-ZnO heteroarchitecture shows enhanced field emission properties such as low turn-on field, high emission current density and better current stability in comparison to other ZnO-based nanostructures. The present CdS-ZnO heteroarchitecture could be extended to other potential applications, such as chemical sensors, photodetectors, optoelectronic devices, and photocatalysts.

Enhanced field emission characteristics of a 3D hierarchical Hfo2-Zno heteroarchitecture - Shisode, Raju T.; Suryawanshi, Sachin R.; Mistari, Chetan D.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
Three dimensional (3D) HfO2-ZnO heteroarchitecture comprised of thin coating of HfO2 on self assembled 3D ZnO urchins with pointed apex has been synthesized using hydrothermal route followed by Pulsed Laser Deposition (PLD). The as-synthesized HfO2-ZnO heteroarchitecture was characterized using XRD, SEM, EDS, and (HR) TEM, in order to reveal its structural, morphological, and chemical properties. The HfO2-ZnO heteroarchitecture emitter exhibits superior field emission (FE) behaviour in contrast to the pristine ZnO urchins, demonstrated by delivery of high emission current density of similar to 885 mA/cm2 at an applied field of similar to 3.35 V/mm, against similar to 383 mA/cm(2) at an applied field of similar to 4.32 V/mu m for the pristine ZnO urchins emitter. Interestingly, the HfO2-ZnO heteroarchitecture emitter exhibits excellent emission current stability characterized with fewer fluctuations, owing to very good ion-bombardment resistance offered by the HfO2 coating. Furthermore, the heteroarchitecture thus obtained facilitates tailoring of the morphology with high aspect ratio and modulation of electronic properties as well, thereby enhancing the FE behaviour. Despite HfO2 being wide band gap and high-k material, the HfO2-ZnO heteroarchitecture exhibits potential as promising candidate for fabrication of high current density cold cathode
Keywords: 3D heteroarchitecture; Field Emission (FE); hydrothermal; PLD; TEM